2016
DOI: 10.1021/acs.est.5b05218
|View full text |Cite|
|
Sign up to set email alerts
|

Smoke in the City: How Often and Where Does Smoke Impact Summertime Ozone in the United States?

Abstract: We investigate the influence of smoke on ozone (O3) abundances over the contiguous United States. Using colocated observations of particulate matter and the National Weather Service Hazard Mapping System smoke data, we identify summertime days between 2005 and 2014 that Environmental Protection Agency Air Quality System O3 monitors are influenced by smoke. We compare O3 mixing ratio distributions for smoke-free and smoke-impacted days for each monitor, while controlling for temperature. This analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 39 publications
6
91
2
1
Order By: Relevance
“…We assign each HYSPLIT point a land-cover type using land-cover classifications from the U.S. Geological Survey (USGS) 2002 North American Land-Cover Characteristics 1 km grid-spacing dataset, created by the National Center for Earth Resources Observation and Science (EROS) as part of the Global Land Cover Characterization Project (Brown, 2016). Land-cover characteristics are assessed using 1 km Advanced Very High Resolution Radiometer (AVHRR) data between 1992 and 1993 using the methods described in Anderson et al (1976).…”
Section: Description Of Land-cover Characteristics Databasementioning
confidence: 99%
See 2 more Smart Citations
“…We assign each HYSPLIT point a land-cover type using land-cover classifications from the U.S. Geological Survey (USGS) 2002 North American Land-Cover Characteristics 1 km grid-spacing dataset, created by the National Center for Earth Resources Observation and Science (EROS) as part of the Global Land Cover Characterization Project (Brown, 2016). Land-cover characteristics are assessed using 1 km Advanced Very High Resolution Radiometer (AVHRR) data between 1992 and 1993 using the methods described in Anderson et al (1976).…”
Section: Description Of Land-cover Characteristics Databasementioning
confidence: 99%
“…Land-cover characteristics are assessed using 1 km Advanced Very High Resolution Radiometer (AVHRR) data between 1992 and 1993 using the methods described in Anderson et al (1976). For this work, we use the GeoTIFF file projected to a latitude-longitude grid as a geospatial raster (Brown, 2016 Hansen et al (2000) for a discussion of the weaknesses of the 1992 land-cover dataset. We have also completed a comparison to a 2010 land-cover dataset, and this comparison is available in the Supplement Sect.…”
Section: Description Of Land-cover Characteristics Databasementioning
confidence: 99%
See 1 more Smart Citation
“…North American fires represent a major source of atmospheric pollutants (Wiedinmyer et al, 2006), and they contribute to elevated ground level ozone (O 3 ) and fine particulate matter (PM 2.5 ) in the U.S. (Baker et al, 2016;Brey and Fischer, 2016;Jaffe et al, 2008;Park et al, 2007;Saide et al, 2015). Exposure to wildfire smoke has been shown to have negative impacts on respiratory and cardiovascular health (Dennekamp and Carey, 2010;Haikerwal et al, 2015;Rappold et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are well-documented case studies of within-plume O 3 production (see Jaffe and Wigder, 2012;Heilman et al, 2014, and references within) and time periods where smoke contributed to exceedances of the US EPA National Ambient Air Quality Standard (NAAQS) for O 3 (Morris et al, 2006;Pfister et al, 2008), currently a maximum daily 8 h average of 70 ppbv. Brey and Fischer (2016) investigated the impacts of smoke on O 3 abundances across the US via an analysis of routine in situ measurements and NOAA satellite products. Their analysis demonstrated that the presence of smoke is correlated with higher O 3 mixing ratios in many areas of the US, and that this correlation is not driven by temperature.…”
Section: Introductionmentioning
confidence: 99%